Biomagnification of mercury in mollusks from coastal areas of the Chinese Bohai Sea1. Issue 50 (4th June 2015) - Meng, Mei; Shi, Jian-bo; Liu, Cheng-bin; Zhu, Na-li; Shao, Jun-juan; He, Bin; Cai, Yong; Jiang, Gui-bin
<x xml:space="preserve">Abstract</x> Biomagnification of methylmercury and growth dilution of inorganic mercury were found during the trophic transfer of mercury in different mollusk species.